Threshold re-encryption based secure deduplication method for cloud data with resistance against side channel attack - Xin TANG; Linna ZHOU; Weijie SHAN; Dan LIU (Tongxin xuebao)
For security and efficiency problems in threshold based deduplication for cloud data,a novel method based on threshold re-encryption was proposed to deal with side channel attacks.A lightweight threshold re-encryption mechanism was presented to transfer the secondary encryption to the cloud for execution and allow clients to generate ciphertext based on key segmentation instead of ciphertext segmentation,both of which largely reduce computational overhead of clients.Also,the proposed mechanism enables clients to decrypt from both one-time encrypted and re-encrypted ciphertext,thus avoiding the overhead of redundant encryption of the same file.Mutual integrity verification between cloud service provider and clients was also supported by the proposed method,which directly ensured the correctness of the correspondence between ciphertext and plaintext on client side.Experiments show that the proposed method not only largely reduces the computational overhead on client side,but also achieves superior storage performance on cloud side simultaneously.